2007
DOI: 10.1093/ps/86.7.1397
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-Dependent Changes in Melatonin Synthesis in the Turkey Pineal Gland and Retina

Abstract: The effect of photoperiod on melatonin content and the activity of the melatonin-synthesizing enzymes, namely, serotonin N-acetyltransferase (AANAT) and hydroxyindole-O-methyltransferase, were investigated in the pineal gland and retina of turkeys. The birds were adapted to 3 different lighting conditions: 16L:8D (long photoperiod), 12L:12D (regular photoperiod), and 8L:16D (short photoperiod). Pineal, retinal, and plasma melatonin concentrations oscillated with a robust diurnal rhythm, with high values during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 58 publications
4
23
1
Order By: Relevance
“…1). Under the three photoperiodic regimes, diurnal dopamine and DOPAC rhythms were out of phase with the demonstrated by us earlier (Zawilska et al 2007) oscillations in retinal melatonin content (Fig. 1).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…1). Under the three photoperiodic regimes, diurnal dopamine and DOPAC rhythms were out of phase with the demonstrated by us earlier (Zawilska et al 2007) oscillations in retinal melatonin content (Fig. 1).…”
Section: Resultssupporting
confidence: 66%
“…In retinas of turkeys held under different light-dark illumination cycles (16L:8D, 12L:12D, and 8L:16D), levels of dopamine and its metabolite DOPAC (present results), and melatonin content (Zawilska et al 2007) showed wellexpressed daily rhythms with opposite phases. High levels of dopamine and DOPAC were observed during the light hours and low levels during the dark hours.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, the key regulatory enzyme in the melatonin biosynthetic pathway is the enzyme AANAT. In fact, biochemical studies revealed the presence of high AANAT mRNA levels in the pineal glands and retinas of vertebrates [47], and changes in melatonin levels reflect oscillations in its activity [43,48]. The enzyme belongs to a superfamily of GCN5-related N-acetyltransferases (GNAT) and need acetyl coenzyme A (AcCoA) as an acetyl group donor [43].…”
Section: Melatonin: Synthesis and Localizationmentioning
confidence: 99%
“…Successful treatment of SAD with bright light therapy, suggests that prolonged melatonin signals after waking contribute to depressive symptoms [18,19]. Individuals with SAD display prolonged periods of elevated melatonin during the winter relative to the summer, similar to changes observed in animals that use photoperiod to time reproduction [18,22,23]. Nondepressed individuals did not display seasonal differences in circulating melatonin concentrations, suggesting a role for melatonin in SAD etiology [18].…”
Section: Introductionmentioning
confidence: 99%